The Holy Spirit and the Soul as Revealed in Nature - Davenport, Nancy (Religion and the arts, 2015)
The artist Anna Lea Merritt (1844–1930) was born in Philadelphia, Pennsylvania and spent most of her professional life in London and in a rural village in Surrey. She settled in England in 1871 and soon became a friend of the members of the Pre-Raphaelite Brotherhood in their mature years, the art critic John Ruskin, the late Victorian artists George Frederick Watts and Frederick, Lord Leighton, and others in the London artistic and literary community. In the milieu she had chosen, her intimate and spiritual relationship with nature and her sympathy for all mankind, ingrained in her in childhood among Unitarians and Quakers in Philadelphia, developed into paintings, murals, and etchings that were at once academic, naturalistic, and mystical. In re-introducing this little known woman artist today, this article focuses on her work as one that evokes the spirit and beauty of the natural world and sympathy for the plight of the suffering, both eloquent testimonials to the ideals and beliefs of her renowned friend and contemporary, John Ruskin and to late Victorian liberal sensibilities.